2015
DOI: 10.1111/eve.12495
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional management of gastric ulceration

Abstract: Summary Gastric ulcers are common in horses and equine gastric ulcer syndrome describes ulcers in the distal oesophagus, nonglandular and glandular stomach as well as the proximal duodenum. Ulcers in the distal oesophagus and nonglandular region of the stomach are probably caused by hydrochloric acid, whereas ulcers in the glandular stomach and proximal duodenum are likely to be caused by a breakdown in the mucosal defence mechanisms. Regardless of the location of ulcers, initial treatment with pharmacological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 91 publications
0
25
0
Order By: Relevance
“…Omeprazole is absorbed in the duodenum and it has recently been suggested that the drug should be administered on an empty stomach . On the other hand, it has also been recommended that keeping the stomach permanently full with forage, feeding forage ad libitum may be beneficial in gastric disease .…”
Section: Discussionmentioning
confidence: 99%
“…Omeprazole is absorbed in the duodenum and it has recently been suggested that the drug should be administered on an empty stomach . On the other hand, it has also been recommended that keeping the stomach permanently full with forage, feeding forage ad libitum may be beneficial in gastric disease .…”
Section: Discussionmentioning
confidence: 99%
“…Clearly there is a role of nutrition in induction and maintenance of squamous gastric ulcers (Andrews et al 2015). In general, for prevention of EGUS/EGSD, a minimum dry matter (DM) intake of ≥ 1.5 % -2 % BW (body weight) (Andrews et al 2015, Harris et al 2017) with an absolute minimum recommendation of 1.25 % DM intake of BW (Har-ris et al 2017) and avoiding long periods of fasting are recommended Coenen 2004, Andrews et al 2015). High forage diets increase chewing activity which is linked to the production of more saliva (Nadeau and Andrews 2009).…”
Section: Introductionmentioning
confidence: 99%
“…High forage diets increase chewing activity which is linked to the production of more saliva (Nadeau and Andrews 2009). However little evidence exists for the exact role of diet (Andrews et al 2015 as well as for the nutritional management in glandular gastric disease (Andrews et al 2015. Nevertheless, it has been suggested that diet might influence the risk for EGGD in a manner similar to EGUS and that the principles for feeding might be the same for horses with squamous and/or glandular disease (Andrews et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is however, well established that chronic use of NSAIDs predisposes to the gastric ulcer Hydrochloric acid is primarily responsible for the ulcers in the distal oesophagus and nonglandular region of the stomach; while breakdown in the mucosal defence mechanisms is responsible for the ulcers in the glandular stomach and proximal duodenum. 6 In ZES, a gastrin secreting tumor of the pancreas stimulates the parietal cells in stomach to increase the acidity, resulting in gastrointestinal mucosal ulceration. This ulcer is refractory to proton pump inhibitor therapy.…”
Section: Introductionmentioning
confidence: 99%